Cultural resources and creative industries in spanish medium-sized cities (Brazilian Geographical Journal, 2012)
In recent years, stress has been put on the relationship between cultural resources and creative industries and their ability to dynamise the economy and generate development processes. At the same time, much geographical research and some public powers and institutions have highlighted the role that medium-sized towns and cities can play by acting as intermediaries between large cities and rural areas. Seeking to combine these two theoretical reference frameworks, this article aims to analyse the presence of cultural resources and creative industries in Spanish medium-sized towns and cities. A typology of these towns and cities is also proposed based on these resources and industries.